PERAN MEDIASI HEDONIC SHOPPING VALUE DALAM PENGARUH PRICE DISCOUNT TERHADAP PEMBELIAN IMPULSIF PADA GENERASI Z - Nayli Nabila; Retna Ngesti Sedyati; Prima Ratna Sari (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study examines the influence of content marketing strategies on social media and digital literacy on cosmetic purchasing decisions among students of the Economics Education Study Program at PGRI Ronggolawe University, Tuban. This study used a quantitative approach with an explanatory design. The sample consisted of 54 students selected using a purposive sampling technique based on specific criteria related to social media use, having seen cosmetic promotional content, and having made cosmetic purchases online. Data were collected through a Likert scale questionnaire and analyzed using descriptive statistics and multiple linear regression with SPSS Version 26. The results showed that content marketing strategies and digital literacy had a significant influence on purchasing decisions with a contribution of 72.1%. Attractive and informative content marketing can increase consumer interest, while digital literacy helps students evaluate information critically before making a purchase. Digital literacy is a more dominant factor in influencing purchasing decisions. This study has limitations in the number of samples and limited coverage of respondents, so further research is recommended to increase the number of samples and other variables such as consumer confidence and E-Wom.